"Born Black and Male": Counseling leaders' self-discovery of strengths. Issue 4 (2nd October 2017) - Roysircar, Gargi; Thompson, Ashland; Boudreau, Melissa
Abstract : Africentric/Afrocentric psychology frames the interview findings on five African-American male leaders in a racial, ethnic, and culturally diverse counseling association. The consensual qualitative research method was used to extrapolate themes from the five interviews. Africentric cultural strengths suggested in the themes are (a) autogeny, (b) primacy of the person in the context of community, (c) consubstantiality of primordial substance, (d) perpetual evolution, and (e) living forever. Two themes related to counseling practice are (f) social justice and (g) cultural empathy. Common trends in statements across interviews are illustrated with rich quotations and summaries. Although the framework of continental African world view facilitated understanding a few African-American male counseling leaders, the study evidences a larger universal human dimension of individuals' pain, resilience, self-discovery of strengths, and leadership bound to a collective self-concept by which leadership can take place both individually and collectively.